المنهج لتعلم اللغة العربية بمعهد النور على ضوء قوة العادة (THE POWER OF HABIT) - Khoirunnisak ilfitriyah Nisak (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mmojokerto, 2021)
The curriculum contains program plans, methods and various things for learning. therefore all teachers and foundation owners must be involved in understanding the curriculum to be designed. learning Arabic at the Annur Islamic boarding school is nothing new. however, it requires the latest innovations in the process of achieving it. namely by making Arabic language curriculum design based on the power of habit.This research is descriptive qualitative, the data collection method uses observation, interviews and documentation. The analysis technique uses data reduction, data presentation and making data conclusions. Conclusion From the results of this study are; first, students lack confidence when speaking Arabic. Second, there is a great deal of concern over mistakes in using Arabic grammar. Third, the lack of opponents to communicate in Arabic (environment).